Digital business platforms and sustainability: a study about sustainable behaviour - Bonetti, Clelia (2020)
As current environmental problems suggest that present consumption and production patterns are not sustainable, technology has received attention as the mediator between scarce resources and continued economic growth. New and ground-breaking sustainable business models are emerging with the potential to realign technological development with sustainable consumption and habit. One of them is the digital platform which has disrupted several industries. As platform-based businesses are rapidly acquiring market share, one could question their role in sustainability. This thesis project focuses on digital platforms for sustainability, and it aims to investigate the features that a digital platform for sustainability should have to develop and support users’ sustainable behaviour. Drawing from the current literature and to answer such a question, a qualitative interviewbased research was performed. The study subject chosen was greenApes, a digital-based certified B corporation that promotes sustainable behaviour via social network. The thematic analysis performed on the 15 interviews’ resulted in five main features, which may play a key role in the context of a digital platform for sustainability: Gamification, Social Network, Community, Clarity and Target. A framework was developed based on these features. Digital platforms for sustainability may use the framework to verify its adequacy in incentivizing sustainable behaviour.